Identification of D-Dimer-E Complex in Disseminated Intravascular Coagulation (DIC) - Whitaker, A.N.; Rowe, E.A.; Masci, P.P.; Gaffney, P.J. (Thrombosis and Haemostasis, 1979)
D-dimer (D2), a product of the plasmin lysis of cross-linked (XL) fibrin, but not of non-XL fibrin or fibrinogen, has been identified in the plasma of patients with DIC due to amniotic fluid embolism. In vitro, D is involved with fragment E as a stable complex (D2-E) but D2 -E has not been identified in vivo before. Fibrin degradation products (FDP) were studied in a patient having fulminant postsplenectomy pneumococcal sepsis and DIC, by immunoprecipitation with anti-fibrinogen (f) and anti-fragment E and characterization by SDS polyacrylamide gel electrophoresis (PAGE). With both antisera soluble HMW fibrin complexes, D2 and E but no X, Y or D were obtained from serum. D2 and E were identified in the supernatant after removing partially XL HMW complexes and fibrinogen from plasma with 2.5 M β-alanine. The presence D antigen in the D2-E complex precipitated by monospecific anti-E was confirmed by crossed Ag-Ab electrophoresis. Crossed Ag-Ab electrophoresis of serum in agarose gave E peaks of slow mobility and no fast-moving free E was found. Thus, D2-E complex exists in vivo and its easy identification, proving the lysis of XL fibrin, would be of value in studying thrombosis. D2-E complex has been identified in other patients with sepsis but at lower concentrations than described above.